2015
DOI: 10.1007/s13410-015-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining diabetes using iris recognition system

Abstract: Iridology is a science which correlates the apparitions of iris to tissue weaknesses in the body. It merely reveals weaknesses, inflammation, or toxicity in organs or tissues. It also indicates weakness long before the symptoms appear. In this paper, support vector machine-based iris recognition system utilizing iridology has been used to determine diabetes. Features from eye image database of 40 people having healthy eye (normal) and having affected eye (diabetes) have been extracted by 2-D wavelet tree. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…The study used eye images features of 80 patients for diabetes diagnosis. The rate of accuracy given by the study was 87.50% 89 . P Samant et al, (2017), diagnose diabetes by analysing iris data of 200 patients using several data mining algorithms such as binary tree, random forest, SVM, neural networks.…”
Section: Rate Of Accuracies Achieved By Analysingmentioning
confidence: 72%
“…The study used eye images features of 80 patients for diabetes diagnosis. The rate of accuracy given by the study was 87.50% 89 . P Samant et al, (2017), diagnose diabetes by analysing iris data of 200 patients using several data mining algorithms such as binary tree, random forest, SVM, neural networks.…”
Section: Rate Of Accuracies Achieved By Analysingmentioning
confidence: 72%
“…In this approach patient can receive the correct treatments based their iris tissues information. This approach is mainly depending on the three important procedures: More insights about the usage of SVM Studies were related to chronic renal failure and the signal in the kidney region A. Bansal, R. Agarwal, R.K. Sharma [23] Using MATLAB for programming for various calculations in pre-processing the image MATLAB, the programming software for numerical and matrix calculation, signal, and graphic processing D. Grayscale adjusted image In the normalization process, the image resolution is decrease in order to complete the operation. The unwanted part of the image that is generated is removed and quality of the image is increased to meet the specified resolution.…”
Section: Iris Design Based On the Clinical Recognition Approachmentioning
confidence: 99%
“…The diseases that are observed are disorders of the stomach. Bansal et al [3] detected a body disorder in iridology using simple image processing in his evidence. The result showed that iridology is an alternative technique that can be used by looking at the iris to find out the status of organs with a very effective introduction algorithm combined with iridology.…”
Section: Introductionmentioning
confidence: 95%